HBV Reactivation in Patients Treated with Antitumor Necrosis Factor-Alpha (TNF-α) Agents for Rheumatic and Dermatologic Conditions: A Systematic Review and Meta-Analysis. (7th July 2014) - Cantini, Fabrizio; Boccia, Stefania; Goletti, Delia; Iannone, Florenzo; Leoncini, Emanuele; Panic, Nikola; Prignano, Francesca; Gaeta, Giovanni Battista
Abstract : Introduction. Antitumor necrosis factor-alpha (TNF- α ) agents are widely used for treatment of rheumatic and dermatological diseases. We conducted the systematic review and meta-analysis to assess the prevalence of HBV reactivation among patients treated with anti-TNF- α . Methods and Findings. A comprehensive literature search of MEDLINE, Scopus, and ISI Web of Knowledge databases was conducted. From 21 studies included in the systematic review, 9 included patients with occult chronic HBV infection and 6 included patients with overt infection while 6 addressed both groups. Based on 10 studies eligible for meta-analysis we report pooled estimate of HBV reactivation of 4.2% (95% CI: 1.4–8.2%, I 2 : 74.7%). The pooled prevalence of reactivation was 3.0% (95% CI: 0.6–7.2, I 2 : 77.1%) for patients with occult infection, and 15.4% (95% CI: 1.2–41.2%, I 2 : 79.9%) for overt infection. The prevalence of reactivation was 3.9% (95% CI: 1.1–8.4%, I 2 : 51.1%) for treatment with etanercept and 4.6% (95% CI: 0.5–12.5%, I 2 : 28.7%) for adalimumab. For subgroup of patients without any antiviral prophylaxis the pooled reactivation was 4.0% (95% CI: 1.2–8.3%, I 2 : 75.6%). Conclusion. Although HBV reactivation rate is relatively low in patients treated with anti-TNF- α for rheumatic and dermatological conditions, the antiviral prophylaxis would be recommended in patients with overt chronic HBV infection.